Inside Back Cover: Dynamic Open Coordination Cage from Nonsymmetrical Imidazole–Pyridine Ditopic Ligands for Turn‐On/Off Anion Binding (Angew. Chem. Int. Ed. 51/2019). Issue 51 (19th November 2019) - Ogata, Daiji; Yuasa, Junpei
Abstract : Nonsymmetrical ligands are usually not considered building blocks for discrete self‐assembled products. In their Communication on page 18424, J. Yuasa and D. Ogata employ a new imidazole/pyridine‐based ditopic ligand as a building block for a dynamic Pd2 L4 open cage compound that is available for turn‐on/off anion binding through stoichiometry‐driven structural transitions.